PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN VO2MAX DALAM PERMAINAN FUTSAL SISWA EKSTRAKURIKULERSMAN 13 MAKASSAR - Mahyuddin, Reza; Munandar, Wahyu (Jurnal Penjaskesrek, 2019)
The purpose of this study for extracurricular activities in SMA Negeri 13 Makassar was obtained by the lack of endurance ability, especially in VO2Max Extracurricular students in futsal sports at SMA Negeri 13 Makassar. find out VO2Max Extracurricular students in futsal sports. This study uses an experimental research design. This research was conducted for 3 months from the initial test to the post test. However, to be able to improve VO2Max that is good, it is necessary to apply appropriate training methods in increasing physical endurance conditions according to the needs of futsal sports, the authors try to apply circuit training methods in increasing VO2Max in futsal games to be able to improve student extracurricular achievements.